2020
DOI: 10.26434/chemrxiv.13238528.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unveiling Structural Disorders in Honeycomb Layered Oxide: Na2Ni2TeO6

Abstract: <b>Honeycomb layered oxides have garnered tremendous research interest in a wide swath of disciplines owing to not only the myriad physicochemical properties they exhibit, but also due to their rich crystal structural versatility. Herein, a comprehensive crystallographic study of a sodium-based Na<sub>2</sub>Ni<sub>2</sub>TeO<sub>6</sub> honeycomb layered oxide has been performed using atomic-resolution transmission electron microscopy, elucidating a plethora of atomic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…σ total shows the maximum (=4.0 × 10 −4 S cm −1 ) in the samples sintered at 750℃, which is 100℃ lower than the condition in previous works 6−11 . Such low sintering temperature compared to other Na‐based oxide solid electrolytes could be useful for co‐sintering with electrode active materials with similar layered structure for fabricating oxide‐based all‐solid‐state SiBs 19−24 . Even for the sample sintered at the lowest temperature of 650℃, σ total = 2 × 10 −4 S cm −1 was obtained.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…σ total shows the maximum (=4.0 × 10 −4 S cm −1 ) in the samples sintered at 750℃, which is 100℃ lower than the condition in previous works 6−11 . Such low sintering temperature compared to other Na‐based oxide solid electrolytes could be useful for co‐sintering with electrode active materials with similar layered structure for fabricating oxide‐based all‐solid‐state SiBs 19−24 . Even for the sample sintered at the lowest temperature of 650℃, σ total = 2 × 10 −4 S cm −1 was obtained.…”
Section: Resultsmentioning
confidence: 65%
“…In the previous works, sintering temperatures of NZTO were commonly set to 850–900℃ 6–11 . However, this sintering temperature may be still high not only for the Na volatilization in the precursor, 10,11 but also for co‐sintering with electrode active materials with similar layered structure for fabricating oxide‐based solid‐state Na batteries 19–24 . In this study, we investigated the sintering temperature dependency on the properties of NZTO.…”
Section: Introductionmentioning
confidence: 99%
“…Grundish et al found that the electrochemical reactivity in Na 3 Ni 1.5 TeO 6 cathode is mainly due to the Ni 2+/3+ redox couple as well as small contribution from Ni 3+/4+ [29]. The splitting in some of the oxidation/reduction peaks observed in the CV curves manifests the presence of different sodium ion disordering in the layered structure [36,37,61]. The appearance of the minor redox peaks can be attributed to the phase transformations during Na + (de)intercalation reactions [38].…”
Section: Bmentioning
confidence: 99%
“…Further, SAED patterns taken along the [100] and [11 ̅ 0] zone axes (Figures 7d and 7e) evidence streaks reminiscent of the modulation in the Na arrangement in Na-rich phase (Na2Ni2TeO6). 57 Whilst only Na-rich phases are observed in TEM measurements, ex situ XRD measurements of discharged electrodes (Supplementary Figure S24) reveal K-rich and mixed alkali phases with Narich phase being predominant. These results reveal that there is a propensity of NaKNi2TeO6 to predominantly reinsert Na ions when cycled in NaK cells.…”
Section: Molecular Dynamics (Md) Simulations Can Avail Insights Into the Microscopic Alkali-ionmentioning
confidence: 99%